Automated Measuring Tool for Handwriting Examination (International Journal of Engineering and Computer Science, 2017)
Handwriting examination is always been a challenge for document expert in court of law. The expert has to form his opinion on the perceptions and observation, however, the need of mathematical or definite calculation is required for a precise and scientific opinion. Automated tool for handwriting examination have always been an area of scientific research in the field of Forensic Document Examination, several models have been reported by many researchers for Optical Character Recognition and few on signature verification but all are very lengthy and need extensive sample size to train the model. However the tool proposed here is developed to measure the pixel distance and compute to calculate angle, and distance which in turn is used to identify the handwriting characteristics.